Abnormal heart rate recovery and chronotropic incompetence on exercise in chronic obstructive pulmonary disease. (August 2013) - Gupta, Mansi; Bansal, Vishal; Chhabra, Sunil K
Chronotropic incompetence (CI; failure to reach the targeted heart rate (HR) on exercise) and a delayed HR recovery (HRR; ≤12 beats decline within the first minute after cessation) reflect autonomic dysfunction (AD) and predict adverse cardiac prognosis. As chronic obstructive pulmonary disease (COPD) is known to be associated with AD, we hypothesized that these patients may manifest these responses on exercise. The prevalence and predictors of these responses in COPD and their association with its severity have not been evaluated. Normoxemic, stable male patients with COPD ( n = 39) and 11 healthy controls underwent lung function testing and incremental leg ergometry. HR responses were monitored during exercise and recovery to compute the HRR and CI. Of all the patients, 33 (84.6%) had at least one of the two exercise responses as abnormal, with the majority (23, 58.9%) having both an abnormal HRR and CI. The frequency of abnormal responses increased with increasing Global Initiative for Chronic Obstructive Lung Disease stage and body mass index, airflow obstruction, dyspnoea and exercise capacity index. After adjusting for smoking history and post-bronchodilator forced expiratory volume in 1 second, only a reduced diffusion capacity for carbon monoxide predicted abnormal HRR, though weakly. We concluded that abnormal HRR and CI are common in patients with COPD. These responses are observed with increasing frequency as the severity of disease increases.